1977
DOI: 10.1128/jb.132.2.370-376.1977
|View full text |Cite
|
Sign up to set email alerts
|

Requirements for induction of the biodegradative threonine dehydratase in Escherichia coli

Abstract: Synthesis of the biodegradative L-threonine dehydratase in Escherichia coli, Crookes strain, was prevented by dissolved oxygen concentrations of 6 ,aM or greater. This effect was shown to be exerted solely on synthesis, rather than being the result of enzyme inactivation in vivo. In addition to an anaerobic environment, maximum enzyme synthesis was dependent upon the presence of a complete complement of amino acids, with omission of L-threonine, L-valine, or L-leucine producing the largest decreases in enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

1977
1977
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…(B) Well 2, Extract from fumarateand cAMP-supplemented AA18 medium (same as well 1 in panel A); wells 4 and 6, extracts from cells grown in AA18 medium with 50 mM fumarate, supplemented with 50 mM glycerol (180 ,jg; specific activity, 0.2) or 50 mM pyruvate (180 ,ug; specific activity, 0), respectively; well 5, 12 ,ug of purified enzyme; wells 1 and 3, buffer. (C) Wells 4 and 6, Extracts from cells grown in AA18 medium supplemented with 50 mM fumarate in the presence (well 4 [180 ,ug; specific activity, 0]) or absence (well 6 [180 ,ug; specific activity, 6]) of pyruvate; wells 1 and 3, 12 ,ug of ptwified enzyme; wells 2 and 5, buffer. (D) Wells 2, 4, and 6, extracts from cells grown aerobically in TYE medium (370 ,ug), H4 medium with fumarate and cAMP (150 pLg), and AA18 medium with fumarate and cAMP (150 ,ug), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(B) Well 2, Extract from fumarateand cAMP-supplemented AA18 medium (same as well 1 in panel A); wells 4 and 6, extracts from cells grown in AA18 medium with 50 mM fumarate, supplemented with 50 mM glycerol (180 ,jg; specific activity, 0.2) or 50 mM pyruvate (180 ,ug; specific activity, 0), respectively; well 5, 12 ,ug of purified enzyme; wells 1 and 3, buffer. (C) Wells 4 and 6, Extracts from cells grown in AA18 medium supplemented with 50 mM fumarate in the presence (well 4 [180 ,ug; specific activity, 0]) or absence (well 6 [180 ,ug; specific activity, 6]) of pyruvate; wells 1 and 3, 12 ,ug of ptwified enzyme; wells 2 and 5, buffer. (D) Wells 2, 4, and 6, extracts from cells grown aerobically in TYE medium (370 ,ug), H4 medium with fumarate and cAMP (150 pLg), and AA18 medium with fumarate and cAMP (150 ,ug), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Despite a large body of information on the control of purified dehydratase at the level of enzyme function (1,3,13,18), the mechanism by which the synthesis of the enzyme is regulated in vivo still remains to be deciphered. Two earlier reports (4,21) on the amino acid requirements for enzyme synthesis in E. coli (Crooks strain) indicated that omitting each of several amino acids, especially threonine, valine, or leucine and possibly serine, aspartate, arginine, and methionine, from a medium containing a synthetic mixture of 18 Lamino acids (AA18) resulted in the greatest reduction of enzyme formation. In a recent study (11) with E. coli K-12 mutants, we found that mutations at multiple loci on the E. coli chromosome influence the expression of the enzyme in vivo.…”
mentioning
confidence: 99%
“…It is also possible that amino acids other than L-threonine or L-serine or both are required for releasing repression of the enzyme synthesis due to oxygen, since this enzyme is produced only under anaerobic conditions (6,10). In this connection, it is noteworthy that Egan and Phillips (1) observed different requirements of amino acids for enzyme induction. It should be pointed out, however, that the apparent discrepancy between their and our studies is probably derived from the different growth conditions of the cells used.…”
Section: Vol 132 1977mentioning
confidence: 99%
“…Biodegradative threonine dehydratase (EC 4.2.1.16) of Escherichia coli and Salmonella typhimurium is subject to multilevel control by several different mechanisms: induction of enzyme synthesis by amino acids and cyclic AMP (8,11,26), catabolite repression by fermentable carbohydrates (11,21,24), allosteric activation by AMP (7,22), inhibition by oa-keto acids (19,22), and catabolite inactivation by intermediary metabolites (9,20). Despite recent attempts, a genetic analysis of three regulatory events has been severely restricted because of the difficulty in selecting mutants, due to lack of scorable phenotype, and the complex medium needed for enzyme induction under a strictly anaerobic environment.…”
mentioning
confidence: 99%